Baicalin alleviates intervertebral disc degeneration by inhibiting the p38 MAPK signaling pathway - Wu, Yating; Li, Fengrui; Shu, Shibin; Feng, Zhenhua; Qiu, Yong; Li, Sen; Zhu, Zezhang (Experimental gerontology, 2025)
Intervertebral disc degeneration (IVDD) represents a prevalent degenerative pathology of the spinal, primarily precipitated by inflammatory processes and the deterioration of extracellular matrix (ECM). Baicalin has an effective anti-inflammatory effect on degenerative diseases. In addition, the P38 mitogen-activated protein kinase (MAPK) signaling pathway plays a crucial role in the pathogenesis of IVDD. To investigate the therapeutic potential of baicalin in modulating pathological changes in IVDD. To design an in vitro model of degeneration of nucleus pulposus cells (NPCs) stimulated by IL-1β and an in vivo mouse model of needling to assess the protective effect of baicalin against IVDD and its underlying mechanism. Baicalin down-regulated inflammatory factors (INOS, COX-2, IL-6) and catabolic factors (MMP-3, MMP-13, ADAMTS-5) while up-regulating anabolic factors (collagen II, SOX-9) by inhibiting the activation of the p38 MAPK signaling pathway, in addition to slowing down the progression of IVDD in the mouse acupuncture model. Our study demonstrated in vitro experiments that baicalin attenuates IL-1β-stimulated IVDD by inhibiting activation of the P38 MAPK signaling pathway. Meanwhile, the effects of baicalin were also confirmed in vivo experiments, Consequently, we propose that baicalin is a promising therapeutic agent for the treatment of disc degeneration. [Display omitted] •Baicalin attenuates IL-1β-induced inflammation and extracellular matrix degradation in nucleus pulposus cells.•Intervertebral disc degeneration is one of the most prevalent age-related diseases•Baicalin delays disc degeneration by inhibiting the P38 MAPK signaling pathway in vitro and in vivo.•Baicalin attenuates disc degeneration in a mouse model in vivo.•Baicalin can be a therapeutic drug for intervertebral disc degeneration.